Investigating Transmission Coefficients of AB-Stacked Bilayer Graphene Nanoribbons with Varied Edge Configurations (ELEKTRIKA- Journal of Electrical Engineering, 2024)
In this study, the transmission coefficients of AB-stacked bilayer graphene nanoribbons (AB-BGNRs) with different edge configurations, specifically zigzag and armchair edges, are comprehensively investigated. These coefficients are modeled and simulated using the tight-binding (TB) model and non-equilibrium Green’s function (NEGF) formalism. The impact of edge structures on the electronic properties of AB-BGNRs is highlighted, providing insights into their potential applications in nanoelectronics devices. Significant variations between zigzag and armchair-edged bilayer graphene nanoribbons (BGNRs) are demonstrated, emphasizing the importance of edge configuration in device performance. This study contributes to the fundamental understanding of edge effects in bilayer graphene and paves the way for the design of more efficient graphene-based electronic devices.
Keywords: BGNRs; edge configurations; NEGF formalism; transmission coefficients; tight-binding model